2009
DOI: 10.1179/14653120723283
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of space available for unerupted permanent canine and premolars in a Nepalese population

Abstract: The newly developed regression equations are more accurate for prediction of width of unerupted permanent teeth in a Nepalese population. Further studies are required based on larger sample size, to confirm the applicability of the new regression equations proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 19 publications
10
19
0
1
Order By: Relevance
“…The combined gender mean values obtained for the mandibular incisors, mandibular and maxillary canines and premolars were similar to reported findings among the Black Americans, Thai, Senegalese and Asian-Americans populations [15,17,25,26]. Sex-specific values revealed higher values among Nigerian subjects compared to Nepalese populations [21] and the teeth sizes are also comparable to the odontometric data reported for Black South Africans [14] who however have slightly larger teeth sizes among the males. This observed variation in tooth sizes in different racial groups further buttresses the need for development of prediction aids for each racial group.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The combined gender mean values obtained for the mandibular incisors, mandibular and maxillary canines and premolars were similar to reported findings among the Black Americans, Thai, Senegalese and Asian-Americans populations [15,17,25,26]. Sex-specific values revealed higher values among Nigerian subjects compared to Nepalese populations [21] and the teeth sizes are also comparable to the odontometric data reported for Black South Africans [14] who however have slightly larger teeth sizes among the males. This observed variation in tooth sizes in different racial groups further buttresses the need for development of prediction aids for each racial group.…”
Section: Discussionsupporting
confidence: 75%
“…The correlation coefficients obtained in this study is comparable to high correlation coefficients in ranges of 0.6 and above reported among American White children [5] Black Americans [15] Thai [17] and Senegalese populations [25] with predominance of higher values in males as also reported in other studies [16,19,25]. However, lower values for correlation coefficients were reported in males among the Thai [17] and Nepalese [21] populations possibly due to gender variability in these populations. The coefficient of determination r 2 of the range of 36% to 44% was observed among the sexes revealing the total variance in canine-premolar widths that could be determined form the knowledge of the combined widths of mandibular incisors.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…(13)(14)(15)(16)(17). On the other hand, applicability of Moyers and Tanaka method has been tested by some researchers and they found that these methods do not truly predict unerupted canine and premolars space in their sample (17).…”
Section: Introductionmentioning
confidence: 99%